Key Financial Metrics Drive Company Value in Indonesia's Retail Sector: Metrik Keuangan Utama Mendorong Nilai Perusahaan di Sektor Ritel Indonesia - Sintya Andriani Fauzi; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the influence of key financial metrics on the value of retail companies in the Indonesian service industry from 2019-2020. Using multiple linear regression analysis on data from 18 companies, the research finds that Total Asset Turnover, Net Profit Margin, and Equity Multiplier positively impact company value, while Return on Investment and Return on Equity do not. These findings suggest that improving asset utilization, profitability margins, and equity leverage can enhance company value, providing valuable insights for company management and investors. Highlights: 1. Total Asset Turnover, Net Profit Margin, and Equity Multiplier increase company value.2. Return on Investment and Return on Equity don't significantly affect value.3. Improve asset utilization, profitability margins, and equity leverage to enhance value. Keywords: Company value, financial metrics, retail industry, asset turnover, profitability